A Conceptual Framework on Impact of Dark Leadership Styles on Organizational Culture and Individual Well Being - Tandon, Pallavi; Mishra, Shikha; Diwan Mehta, Jyotsna (International Journal of Psychosocial Rehabilitation, 2020)
The review paper on dark leadership styles aims to establish the relationship between core elements of study, namely, dark leadership styles, organizational culture, and individual well-being. The paper comprises an extensive review of existing literature in the realm of dark leadership styles in order to draw the direct relationship between the variables and hence add to the humongous study of the negative side of leadership styles. Dark leadership styles have far-reaching, deep-seated psychological consequences on the well-being of an individual. A negative leader with his negative traits can render an organization nonfunctional and nonexistent.